ANALISIS KESINAMBUNGAN MATA KULIAH KEPAMONGPRAJAAN - Marja Sinurat; Yusharto Huntoyungo (Institut Pemerintahan Dalam Negeri, 2017)
The success of education management is determined by the accuracy of curriculum in order to create the simultaneous and cohesive among subjects as the main input for the education program itself. At this stage, the issues of creating a simultaneous program are how to design the curriculum, how educators engage or involve to analyse the simultaneous among the subjects, and how prepared the educators in managing the curriculum so that this can be reflected on the students’ competencies level. All the questions above has been researched and it is concluded that the educators are obliged to be engaged or involved in analysing the simaltenous subjects in order to design the curriculum as well as the implementation in class. Keywords: education, subjects, curriculum